Extracellular vesicles and exosome-like nanovesicles as pioneering oral drug delivery systems - Mondal, Jagannath; Pillarisetti, Shameer; Junnuthula, Vijayabhaskarreddy; Surwase, Sachin S.; Hwang, Seung Rim; Park, In-Kyu; Lee, Yong-kyu (Frontiers in Bioengineering and Biotechnology, 2024)
As extracellular vesicle (EV)-based nanotechnology has developed rapidly, it has made unprecedented opportunities for nanomedicine possible. EVs and exosome-like nanovesicles (ELNVs) are natural nanocarriers with unique structural, compositional, and morphological characteristics that provide excellent physical, chemical, and biochemical properties. In this literature, we examine the characteristics of EVs, including how they are administered orally and their therapeutic activity. According to the current examples of EVs and ELNVs for oral delivery, milk and plant EVs can exert therapeutic effects through their protein, nucleic acid, and lipid components. Furthermore, several methods for loading drugs into exosomes and targeting exosomes have been employed to investigate their therapeutic capability. Moreover, we discuss EVs as potential drug carriers and the potential role of ELNVs for disease prevention and treatment or as potential drug carriers in the future. In conclusion, the issues associated with the development of EVs and ELNVs from sources such as milk and plants, as well as concerns with standardized applications of these EVs, are discussed.